Central Nervous System Hemorrhages Induced by Heparin in Rats with Allergic Encephalomyelitis - Levine, S; Wenk, E. J (Thrombosis and Haemostasis, 1966)
Many cases of acute necrotizing hemorrhagic encephalopathy have massive hemorrhages. The experimental model for this disease, hyperacute allergic encephalomyelitis, has only microscopic hemorrhages. Treatment of affected rats with heparin converted microscopic to massive hemorrhages, thus completing the analogy between human and experimental diseases. There was no evidence that hemorrhage can precede inflammation. Nor were hemorrhages observed in the ordinary form of allergic encephalomyelitis, in which permeability changes were less profound.